Tensile strength assay comparing the resistance between two different autologous platelet concentrates (leucocyte-platelet rich fibrin versus advanced-platelet rich fibrin): a pilot study - Martim de Almeida Nóbrega Correia Pascoal; Nuno Bernardo Malta dos Santos; António Manuel Godinho Completo; Gustavo Vicentis de Oliveira Fernandes (SpringerOpen, 2021)
Abstract Background Since the leucocyte-platelet rich fibrin (L-PRF) was published in 2001, many studies have been developed, analyzing its properties, and also verifying new possibilities to improve it. Thereby, it emerges the advanced-platelet rich fibrin (A-PRF) with a protocol that optimizes the properties obtained by the L-PRF. Nonetheless, there is a gap in the literature to landmark the evolutive process concerning the mechanical properties in specific the resistance to tensile strength which consequently may influence the time for membrane degradation. Thus, this study had the goal to compare the resistance to the traction of membranes produced with the original L-PRF and A-PRF protocols, being the first to this direct comparison. Findings The harvest of blood from a healthy single person, with no history of anticoagulant usage. We performed the protocols described in the literature, within a total of 13 membranes produced for each protocol (n = 26). Afterward, the membranes were prepared and submitted to a traction test assessing the maximal and the average traction achieved for each membrane. The data were analyzed statistically using the unpaired t test. Regarding average traction, A-PRF obtained a value of 0.0288 N mm−2 and L-PRF 0.0192 N mm−2 (p < 0.05 using unpaired t test). For maximal traction, A-PRF obtained 0.0752 N mm−2 and L-PRF 0.0425 N mm−2 (p < 0.05 using unpaired t test). Conclusion With this study, it was possible to conclude that indeed A-PRF has a significative higher maximal traction score and higher average traction compared to L-PRF, indicating that it had a higher resistance when two opposing forces are applied.